Almost sure invariance principle for random piecewise expanding maps. (10th April 2018) - Dragičević, D; Froyland, G; González-Tokman, C; Vaienti, S
Abstract: We prove a fiberwise almost sure invariance principle for random piecewise expanding transformations in one and higher dimensions using recent developments on martingale techniques.